The effect of magnesium vacancies on the intraband scattering in MgxB2 as determined by point contact Andreev reflection - Yates, Karen A.; Miyoshi, Y.; Grunwell, J.; Riggall, K.; Cohen, L. F.; Chen, Soo Kien; MacManus Driscoll, Judith L.; Serquis, Adriana (American Institute of Physics, 2007)
In order to introduce structural defects into the band with minimal distortions in the band, bulk samples of varying magnesium content were prepared. Point contact Andreev reflection measurements reveal that the density of states of the band and the behavior of the energy gaps in field imply a relative increase of band to band scattering with increasing magnesium deficiency. The results are consistent with the observed increase of the low temperature Hc2 value in magnesium deficient MgB2.